When Does Voice Lead to Exit? It Depends on Leadership - McClean, Elizabeth J.; Burris, Ethan R.; Detert, James R. (Academy of Management Journal, 2013)
We examine the unit-level relationship between employee voice and exit with multisource data collected over two time periods in 136 restaurants. We find that three managerial characteristics that signal the ability and willingness to engage in change—management team change orientation, manager participation in decision making, and manager access to organizational resources—moderate the unit-level relationship between voice and exit: Employee voice is positively related to turnover when each of these factors is low and negatively related to turnover when each is high. Implications for research on voice, leadership, and turnover are discussed.